Utilization of antenatal care and out of pocket expenditure on delivery care in Dakshina Kannada - Tellis, Sharal B.; Rent, Priyanka D.; Dmello, Mackwin K. (International Journal Of Community Medicine And Public Health, 2018)
Background: Maternal health refers to the health of women during pregnancy, childbirth and the postpartum period. Factors like education, economic status and out of pocket (OOP) expenditure can affect utilization of maternal health services. Hence this study aims to assess the utilization pattern of maternal health care and the out of pocket expenditure for delivery services in a public maternity hospital. Methods: A cross sectional study was conducted using primary data from women who delivered in public maternity hospital, Mangaluru during January –February 2018. Study respondents were interviewed using pre-tested, interview schedule. The data was analysed using SPSS 20.0 version. Results: 78.3% of the respondents visited the health care provider during first trimester of pregnancy. 97.3% of the mothers attended ≥4 antenatal visits. The time of the first ANC visit, consumption of Iron folic acid (IFA) tablets, choice of provider for ANC are significantly associated with caste, education of the respondents and their husbands. The mean expenditure for delivery care, including indirect expenditure was ₹2875. Expenditure during delivery was significantly associated with respondent’s education and type of delivery. Conclusions: Socio demographic characteristics like caste and education did seem to have an effect on the utilization of ANC especially consumption of IFA. Education and communication campaigns may aid to improve this. Good implementation of government schemes can help to reduce the direct OOP expenditure for delivery care. The indirect cost associated with maternity care may still be a burden for poor families.